On-farm resource-use efficiency in China: overall rebounding trends and region-specific enhancement opportunities - Meng-Lu Huang; Jing-Yu Liu; Xiaoxi Wang; Huijuan Dong; Zhipin Ai (Humanities & Social Sciences Communications)
Abstract China’s agricultural sector has undergone substantial expansion in terms of crop production and resource inputs, giving rise to complex challenges, including resource scarcity, carbon emissions, and ecological degradation. Sustainable development of the agricultural sector largely hinges on a well-functioning food-energy-water (FEW) nexus because agriculture is closely intertwined with these resources. However, little attention has been paid to on-farm resource-use efficiency (RUE) in relation to the FEW nexus. We established an output-input framework based on provincial crop production, machinery, fuel, fertilizers, manpower, pesticide, seed, water use, and land use in China from 1987 to 2020. In accordance with this framework, we quantified on-farm RUE for 31 provinces. Our findings indicate that the degree of agricultural intensification declined after 2017 and that overall RUE exhibited a U-shaped pattern of decreases followed by increases, with the peak RUE value recorded in 2020. Although technological advancement has increased RUE and mitigated the adverse effects of agricultural intensification, it cannot guarantee resource-saving or land-sparing. This finding has important policy implications for achieving sustainable socio-ecological systems and underscores the urgent needs of implementing cross-sectoral and region-specific policies to achieve regional RUE improvement and subsequent sustainable intensification. A comprehensive approach grounded in a nexus mode of thinking that includes both technological advancement and policy intervention is required to ensure the environmental sustainability of agricultural systems and effectively address future food security demands.